Cotton Mather, Jonathan Edwards, and the Quest for Evangelical Enlightenment: Scripture and Experimental Religion - Hoselton, Ryan P. (Springer Nature Switzerland, 2023)
Chapter 1. Introduction: Spiritually Discerned -- Chapter 2. “Search the Scriptures; Search Your Experiences”: Reading the Bible Spiritually from the Reformation to Early Evangelicalism -- Chapter 3. “Experimental Christians”: Mather’s Philosophical and Biblical Vitalism -- Chapter 4. “Evangelical Illustrations”: Mather’s Experimental Exegesis -- Chapter 5. “Complex Spiritual Ideas”: Edwards, the Spiritual Sense, and Scripture -- Chapter 6. “It Wonderfully Enlightens”: Edwards’ Exegesis of Sensation -- Chapter 7. Conclusion./.
Dissertation eingereicht unter dem Titel: Spiritually discerned: Cotton Mather, Jonathan Edwards, and experiential exegesis in early evangelicalism
Keywords: Hochschulschrift; Edwards, Jonathan; Mather, Cotton; Evangelikale Theologie; Protestantismus; USA